Analisis Tindak Tutur Komisif pada Monolog Demokrasi Karya Putu Wijaya - Anggia Puteri; Muhammad Khoir Pahlepi; Rika Arini; Ahmad Bukhari Nasution; Nurul Hijrah; Diva Azzurra; Adelia Fitri Anggita; May Sarah; Jelita Teresia Br L. Tobing (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to analyze commissive speech acts in Putu Wijaya's democracy monologue. Commissive speech act is a speech act that binds the speaker to carry out what is mentioned in the speech. This research uses descriptive qualitative method which is a research that describes the phenomenon or situation that is observed objectively. The subject of this research is the video monologue "Democracy" by Putu Wijaya by students of SMAN 5 Surakarta. This research uses data collection techniques, namely listening and note-taking techniques. The listening technique is done repeatedly to get precise and accurate data. Furthermore, the results of listening to the data were collected by recording. The data analysis used is data reduction, data presentation, and conclusion drawing. The results show that the use of commissive speech acts in Putu Wijaya's “Democracy” monologue shows how speech functions to express the speaker's commitment to the spoken statement. Such as intending, promising, swearing, realizing, bargaining, and refusing.